2005
DOI: 10.1007/s11897-005-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions and detours in the myocardial matrix highway and heart failure

Abstract: Myocardial remodeling invariably occurs in congestive heart failure (CHF) and is a response to a prolonged cardiovascular stress, which is characterized by a cascade of compensatory structural events. Remodeling of the myocardial interstitium occurs in CHF and likely contributes to the progression of the remodeling process. The myocardial matrix can be considered a biological highway in which a large amount of signaling proteins and structural proteins are being moved within the interstitium, entering and exit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Recent studies have demonstrated that fibroblasts have other critical functions other than ECM synthesis, deposition and remodeling 173 . Cardiac fibroblasts have a high membrane resistance, which makes them good conductors.…”
Section: Cardiac Fibroblasts and Electrical Signalingmentioning
confidence: 99%
“…Recent studies have demonstrated that fibroblasts have other critical functions other than ECM synthesis, deposition and remodeling 173 . Cardiac fibroblasts have a high membrane resistance, which makes them good conductors.…”
Section: Cardiac Fibroblasts and Electrical Signalingmentioning
confidence: 99%
“…Cardiac diseases (CD) frequently progress into heart failure. Progression of CD may result from multiple myocardial remodeling events, initially as beneficial adaptive changes, but eventually resulting in dysregulation of collagen synthesis and heart failure . Chronic heart failure is associated with enhanced catabolic metabolism finally resulting in overall weight loss and cardiac cachexia …”
mentioning
confidence: 99%
“…Progression of CD may result from multiple myocardial remodeling events, initially as beneficial adaptive changes, but eventually resulting in dysregulation of collagen synthesis and heart failure. [1][2][3] Chronic heart failure is associated with enhanced catabolic metabolism finally resulting in overall weight loss and cardiac cachexia. 4 Leptin, an adipokine, influences body weight and regulates energy homoeostasis by decreasing appetite and increasing basal metabolic rate.…”
mentioning
confidence: 99%
“…This study confirmed that chronic hypoxia breaks the delicate balance of proteolytic and anti-proteolytic forces during lung development, which accounts for several pulmonary pathologies, including pulmonary fibrosis. The TIMP-1:MMP-1 ratio was also remarkably increased in patients with severe left ventricular hypertrophy, showing that the interaction of TIMP-1 with another MMP besides MMP-9 also has a significant role in the pathophysiological remodeling [80]. The disruption of fine dynamics of MMP–TIMPs by acute hypoxia is also supported by studies using a neonatal hypoxic ischemia (HI) model.…”
Section: The Role Of Mmps and Timps In Hypoxia-induced Abnormal Heartmentioning
confidence: 99%